POLITICAL PLURALISM AND MULTIPARTY - Erhard NICULESCU (Challenges of the Knowledge Society)
Political parties have made themselves noticed in history by competing for power and over time they have emerged as undeniable and indispensable realities in a political system regardless of its form. The Constitution of Romania recognised the role and historical importance of pluralism and political parties and dedicated them a place of honour in the general principles that establish our state as a democratic and social state of law. This article analyses the constitutional provisions on political parties, depicting the evolution of statutory regulations thereon over more than 100 years, during various political regimes. Last but not least, it also analyses concepts and points of view of the doctrine with respect to the subject matter, while also making references to the relevant constitutional jurisprudence. Finally, as a result of the analysis conducted, we will reveal any weaknesses of the legislation and we will make our conclusions.